(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2024)
The main purpose of this study was to compare student evaluation (STEV), peer evaluation (PEEV) and self-evaluation (SEEV) of mathematics teacher effectiveness in Public Senior Secondary Schools in Sardauna Local Government Area of Taraba State. The research design adopted was survey design; this is because the researchers were interested in comparing three methods of evaluating teacher effectiveness. The population for the investigation consisted of all Mathematics teachers of senior secondary schools, all senior secondary school students who offer Mathematics in Sardauna Local Government Area. The sample for the investigation consisted of 9 Mathematics teachers, 18 peers of the Mathematics teacher and 180 Mathematics students selected through multi-stage stratified sampling technique from nine (9) senior secondary schools designated ‘Special Science Secondary Schools’ located across the Educational Zones in Sardauna Local Government Area of Taraba State. Three questionnaires were employed for data collection. They were: Student Evaluation of Teacher Effectiveness Instrument (STEV), Peer Evaluation of Teacher Effectiveness Instrument (PEEV) and Self Evaluation of Teacher Effectiveness Instrument (SEEV). Each of the questionnaires designed by the researchers consisted of 2 sections: the essential bio-data and 24 items on a five-point (5-point) scale. The major findings revealed that, there is a significant difference between mean scores of students, peers and self-evaluation of mathematics effectiveness in Sardauna Local Government Area of Taraba State secondary schools. There is no significant difference between the mean score and the mean score of peers of the Mathematics teacher in Sardauna Local Government of Taraba State secondary schools. Based on the findings, it has been shown empirically that the three methods yielded an average score of 55% this indicates that the teachers are effective in their instructional delivery; however, the teachers need to put more effort on teaching Mathematics. Based on the findings, the following recommendations were made; Schools in Sardauna LGA should ensure regular inspection of their teachers to monitor their instructional delivery using the combination of two methods for both formative and summative purposes.